2023
DOI: 10.3389/fonc.2023.1132559
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the mitophagy-related diagnostic biomarkers in hepatocellular carcinoma based on machine learning algorithm and construction of prognostic model

Abstract: Background and aimsAs a result of increasing numbers of studies most recently, mitophagy plays a vital function in the genesis of cancer. However, research on the predictive potential and clinical importance of mitophagy-related genes (MRGs) in hepatocellular carcinoma (HCC) is currently lacking. This study aimed to uncover and analyze the mitophagy-related diagnostic biomarkers in HCC using machine learning (ML), as well as to investigate its biological role, immune infiltration, and clinical significance.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…A previous study has reported that SERPINE1 facilitated HCC progression ( Li et al, 2021 ). SPP1 and CYP2C9 have also been as prognostic biomarkers for HCC ( Tu et al, 2023 ). CCNB1 can promote cell proliferation, migration, invasion and resistance in HCC ( Gu et al, 2019 ; Jin et al, 2020 ; Xia et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has reported that SERPINE1 facilitated HCC progression ( Li et al, 2021 ). SPP1 and CYP2C9 have also been as prognostic biomarkers for HCC ( Tu et al, 2023 ). CCNB1 can promote cell proliferation, migration, invasion and resistance in HCC ( Gu et al, 2019 ; Jin et al, 2020 ; Xia et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%